Pseudo-fractional differential equations and generalized g-Laplace transform - Sousa, J. Vanterler da C.; Camargo, Rubens F. [UNESP]; de Oliveira, E. Capelas; Frederico, Gastáo S. F. (Springer Nature, 2021)
In this article, we introduce a generalized g-Laplace transform and discuss some essential results of integral transform theory, in particular, involving a ψ-Hilfer pseudo-fractional derivative and function convolution. In this sense, we investigated the existence and uniqueness of known solutions for a pseudo-fractional differential equation.
Keywords: Existence and uniqueness; g-Laplace transform; Pseudo-fractional operator